Analysis of Odor Distribution in Urban Landscape With GIS - Çeven, Elif Ayan; Belkayalı, Nur; Aydın, Miraç (Springer Science and Business Media LLC, 2022)
Abstract
A component of urban landscape, smell sources affect the urban atmosphere based on various activities. In this atmosphere, several unpleasant odors and pleasant smells are present and dispersion of these smells vary based on spatial attributes. Thus, in the present study, urban smellscapes in Kastamonu province urban center with various smellscapes and diverse physical structure were determined with human evaluator and smell measurement device to determine whether urban physical structure and climatic factors were effective on the dispersion modeled with the IDW method in GIS. Since the odor density changes depending on temperature and humidity, the study was carried out in all seasons for 1 year and serial measurements were analyzed for 1 month in August in the most suitable climatic period. The study findings demonstrated that smell sources and intensity varied based on spatial and climatic properties on a route with different occupancy types; thus, smell did not affect the space at different point but as an area. Therefore, the element of smell should be integrated into planning and design work based on the dispersion property of smell.
Keywords: 13. Climate action; 11. Sustainability